Contactin-associated protein-2 antibodies in non-paraneoplastic cerebellar ataxia. - Becker, E; Zuliani, L; Pettingill, R; Lang, B; Waters, P; Dulneva, A; Sobott, F; Wardle, M; Graus, F; Bataller, L; Robertson, N; Vincent, A (2012)
Relatively few studies have searched for potentially pathogenic antibodies in non-paraneoplastic patients with cerebellar ataxia.